Thermal performance evaluation of building with vertical fences of reinforced concrete cast in loco (Research, Society and Development, 2022)
Studies carried out in the last decade, based on the thermal performance evaluation procedures of NBR 15.575/2013, emphasized the low performance of cast-in-place reinforced concrete walls in some climatic conditions in Brazil. Due to the criticism directed at such procedures, in 2021, an amendment was published altering the old methods of evaluating the thermal performance of buildings of the aforementioned standard, therefore requiring the corresponding updates for new projects. The article aims to evaluate the thermal performance of a single-family housing project with vertical fences made of reinforced concrete cast in loco, within the climatic conditions of the municipality of Paulo Afonso-BA, based on the new procedures of the performance standard of buildings. As for the methodological procedures, the EnergyPlus software was used to perform a computer simulation of a single-family housing project, admitting two values of solar absorptance for the roof, that is, MReal1 with α = 0.2 and MReal2 with α = 0, 4. The percentage of transparent elements and ventilation, present in the house design, contribute to a lower thermal performance in the living room and bedroom 2, seen in the results obtained by both methods. However, it is concluded with the computational simulation method, that a superior thermal performance can be achieved by changing the color of the roof to a light color.